VOLKSMED Database: A Source for Forgotten Wound Healing Plants in Austrian Folk Medicine - Eichenauer, Elisabeth; Saukel, Johannes; Glasl, Sabine (Planta Medica, 2024)
The global increase in the incidence of wounds is concerning and fuels the search for new treatment options. The use of traditional medicinal plants in wound healing represents an appreciated available therapeutic possibility. This work introduces the VOLKSMED database, which contains plants and other materials used in Austrian folk medicine, either as monographs or mixtures. This work focuses on the monographs of the database. Concerning wound healing, Hypericum sp., Arnica montana, Calendula officinalis, Plantago sp., and Malva sp. are the most commonly used plants. The focus of this paper is set on selected lesser-known plants (Abies alba, Anthyllis vulneraria, Brassica sp., Gentiana sp., Larix decidua, Picea abies, Sambucus sp., Sanicula europaea) and their status quo in literature concerning wound healing. A systematic search using the databases SciFinder, SCOPUS, and PubMed yielded substantial evidence for the wound healing potential of Brassica sp., Gentiana sp., the Pinaceae A. abies, L. decidua, and P. abies, as well as Sambucus nigra. In vivo and clinical studies substantiate their use in Austrian folk medicine. According to the literature, especially A. vulneraria, Sambucus racemosa, and S. europaea would be worth investigating in-depth since data concerning their wound healing effects – even though scarce – are convincing. In conclusion, the VOLKSMED database contains promising opportunities for further treatment options in the field of wound healing. Future research should consider the listed plants to support their traditional use in Austrian folk medicine and possibly promote the implementation of old knowledge in modern medicine.
Keywords: Austrian folk medicine; wound healing; medicinal plants; VOLKSMED database